Lessons in learning, e-learning, and training : - Schank, Roger C. (Pfeiffer, 2005)
From Roger C. Schank—one of the most highly respected thinkers, writers, and speakers in the training, learning, and e-learning community—comes a compelling book of essays that explore the myriad issues related to challenges faced by today’s instructional designers and trainers. The essays offer a much-needed perspective on what trainers do, why they do it, and how they do it. Lessons in Learning, e-Learning, and Training serves as a barometer to the issues that often perplex trainers and helps to illuminate three main points: what can and cannot be taught; how people think and learn; and what technology can really effectively provide. In addition, each essay is filled with practical guidance and includes a summary of ideas, tips and techniques, things to think about, checklists, and other job aids.